2022
DOI: 10.3389/fimmu.2022.838636
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Transcriptome and Surface Epitope Analysis of Ankylosing Spondylitis Facilitates Disease Classification by Machine Learning

Abstract: Ankylosing spondylitis (AS) is an immune-mediated inflammatory disorder that primarily affects the axial skeleton, especially the sacroiliac joints and spine. This results in chronic back pain and, in extreme cases, ankylosis of the spine. Despite its debilitating effects, the pathogenesis of AS remains to be further elucidated. This study used single cell CITE-seq technology to analyze peripheral blood mononuclear cells (PBMCs) in AS and in healthy controls. We identified a number of molecular features associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Moreover, the evaluation of distinct comorbidities and complications, sites of infection, types of pathogens, antibiotic therapy, hypoglycemic agents, and comprehensive treatment strategies might help to understand individual variations of a given patient and subgroups. More importantly, more detailed monocyte classifications could be performed using single-cell RNA sequencing approaches ( 55 ). A most important limitation of the current study is the low number of patients in defined subgroups such as non-diabetic, obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the evaluation of distinct comorbidities and complications, sites of infection, types of pathogens, antibiotic therapy, hypoglycemic agents, and comprehensive treatment strategies might help to understand individual variations of a given patient and subgroups. More importantly, more detailed monocyte classifications could be performed using single-cell RNA sequencing approaches ( 55 ). A most important limitation of the current study is the low number of patients in defined subgroups such as non-diabetic, obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Riel et al used computed tomography (CT) to construct an early diagnosis model using machine learning methods [ 47 ]. Samuel et al used single-cell transcriptome and surface epitope analysis of AS to classify diseases using machine learning methods [ 48 ]. Liang et al used LASSO regression to find that the severity of the platelet-to-lymphocyte ratio was related to the severity of AS, which is helpful for diagnosing and treating physicians [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term spondyloarthritis covers a heterogeneous set of conditions that can involve a variety of tissue ( Sharip and Kunz, 2020 ) including joints and the spine, specifically the sacroiliac joints ( Brown et al, 2020 ; Xiong et al, 2022 ). These inflammatory immune-mediated conditions can affect spinal tissues especially support tissues such as ligaments and their entheses of the axial skeleton ( Alber et al, 2022 ; Li et al, 2022 ). Long considered mainly a disease of men, particularly ankylosing spondylitis, has more recently been reported to also affect a subset of females ( Masi, 1992 ; Wright et al, 2020 ; Cunha et al, 2022 ; Marzo-Ortega et al, 2022 ; Stovall et al, 2022 ).…”
Section: Influence Of Sex On Msk Tissues As An Adultmentioning
confidence: 99%
“…The onset and progression of the axial spondyloarthritis spectrum of diseases clearly has a genetic basis ( Brown et al, 2020 ), with association with HLA B27 ( Masi, 1992 ; Diaconu et al, 2022 ). Recent attempts to identify biomarkers of disease subtypes has progressed ( Akhtari et al, 2020 ; Alber et al, 2022 ), as well as insights into inflammatory mechanisms ( Lee et al, 2022b ). In addition, recent information has revealed that the gut microbiome of patients is different from a healthy control population, but no sex differences were noted ( Wang et al, 2022 ).…”
Section: Influence Of Sex On Msk Tissues As An Adultmentioning
confidence: 99%